Organizations : structures, processes, and outcomes. (10th ed.) - Tolbert, Pamela S ; Hall, Richard H., 1934- (Pearson/Prentice Hall, 2020)
This edition of Organizations: Structures. Processes, and Outcomes has undergone yet another major revision. The changes that we’ve made were guided by three aims: (1) to provide readers with a better sense o f the historical development o f ideas and concerns that underpin contemporary arguments and debates on the topics that we cover, (2) to update our coverage of research and theorizing on these topics, and (3) to discuss some new lines of research and theory on organizations that we view as especially provocative and promising.Thinking about organizations -- Organizational structure : key dimensions -- Organizational structure : explanations -- Power and power outcomes -- Leadership -- Decision-making -- Communication -- Managing organizational environments : conceptions of the environment -- Managing organizational environments : general paradigms -- Organizational performance and change.